Answer
given,
[tex]f(x) = \dfrac{-e^x}{x - 4}[/tex]
to find the critical point of the given expression
fist differentiating the function
[tex]f'(x) = -\dfrac{(x-4)e^x+ e^x}{(x - 4)^2}[/tex]
[tex]f'(x) = \dfrac{-(x-4)e^x- e^x}{(x - 4)^2}[/tex]
[tex]f'(x) = \dfrac{-e^x(x-3)}{(x - 4)^2}[/tex]
now equating differential equation to zero
[tex] \dfrac{e^x(-x+3)}{(x - 4)^2}=0[/tex]
[tex] e^x(-x+3)=0[/tex]
now,
-x + 3 = 0 and eˣ ≠ 0
x = 3
the critical number will be equal to x = 3
[tex]y = \dfrac{-e^3}{3 - 4}[/tex]
[tex]y =e^3[/tex]